Does International Trade Affect Structural Change? - Mesa Salamanca, Camilo Andres; Llanez Anaya, Helmer Fernando (Review of Economic Analysis, 2025)
We analyze the effects of international trade on structural change. We show a positive correlation between openness and the share of the agricultural sector for developing economies and present a model to rationalize this stylized fact. We built a two-sector model to compare the autarky and open economy equilibrium. The results indicate that, for developing economies, international trade may delay structural change. If the comparative advantage is in agricultural goods, trade leads to greater specialization in this kind of goods and lower participation of other goods.